OLAP TECHNOLOGY AS DECISION-MAKING SUPPORT TOOL - D. V. Akushko (Литьë и металлургия, 2017)
The present article discloses the basic principles of work with OLAP technologies, shows key features in comparison with traditional systems of the reporting. The simplified structure of an OLAP cube for the analysis of cost of products of the steelsmelting shop is considered.